Analisis Program Corporate Social Responsibility (CSR) Studi Kasus Pada PT. Karya Cemerlang Persada Terhadap Sosial, Ekonomi Dan Lingkungan Masyarakat - Muhammad Safri; Butsiardin Siregar; Sa’ad Murdy (Jurnal Dinamika Manajemen, 2023)
In order to reduce negative impacts and increase the positive impact of coal mining business activities, company responsibility is not just economic activities that generate profit for business continuity, but also social and environment responsibility. CSR program implemented by the company to reduce the negative impact. This study aims to analysis Corporate Social Responsibility (CSR) program of coal mining company PT. Karya Cemerlang Persada to social, economic and environmental community by analyzing the success of the CSR program and analyzing the community's satisfaction with the CSR program in Tanjung Belit Village, Bungo Regency, Jambi Province. The approach used in the research is quantitative comparing the plan with the realization of the CSR program and calculating the level of satisfaction community to activities by the company in terms of economic, social and environment. Respondents from this study were 80 respondents who came from communities affected by mining activitiy. The results of this study is the percentage achievement of budget realization is above than threshold set by the Ministry of Energy and Mineral Resources (ESDM). This study also shows that CSR activities give a big influence ecause it has increased people income in Pemusiran, and community satisfaction on CSR activities conducted by the company is good to realize the sustainability the results of corporate CSR program.